Kontruksi Kolokasi dalam Iklan: Kajian Semantik - Fitri Junianti Girsang; Dairi Sapta Rindu Simanjuntak; Lidia Nuryani Situmorang; Juindah Sri Naomi Simanungkalit (Paedagogie, 2026)
This study aims to examine the construction of collocations in the language of shampoo, soap, fabric softener, and cosmetic product advertisements. The method used is descriptive qualitative with data in the form of verbal utterances of advertisements collected through documentation techniques and limited corpus recording. The analysis was carried out by identifying and classifying lexical and grammatical collocations and interpreting their meanings. The results of the study indicate that lexical collocations are more dominant, especially in the patterns of verb + noun, noun + adjective, and adjective + noun, which function to strengthen persuasive messages and brand image.